Efficacy study of edaravone and acetylcysteine towards bleomycin-induced rat pulmonary fibrosis - Yu, Wen-Cheng (Int J Clin Exp Med, 2015)
The aim of this study was to investigate the interventional effects of Edaravone (EDA) and Acetylcysteine (NAC) towards the Bleomycin (BLM)-induced pulmonary fibrosis. 48 Wistar rats were divided into the control group, the BLM group, the hormone group, the EDA group, the NAC group and the combination group. After performing the BLM intratracheal injection to prepare the pulmonary fibrosis model, the rats were administrated EDA, dexamethasone (DEX), NAC and EDA+NAC combined intervention, the lung HRCT examination was performed on the 7(th), 21(st) and 31(st) day. On the 31(st) day, the rats were killed for the detection of serum malondialdehyde (MDA) and superoxide dismutase (SOD) contents; the lung tissues were performed the HE and Masson staining and determined the hydroxyproline content. The rats of the intervention group exhibited mild hypoxic phenomenon, with less ground-glass shadow and consolidated shadow than the BLM group, the MDA content decreased while the SOD content increased, and the degrees of alveolar inflammatory cell infiltration and fibrosis were low. The results of the EDA group and the NAC group were similar, and those of the combination group were better. EDA could inhibit the BLM-induced pulmonary fibrosis through adjusting the oxidant/antioxidant imbalance, with the effect similar to NAC, and the combined application of these 2 drugs were much more effective.